Pengaruh Metode CIRC Terhadap Kemampuan Membaca Pemahaman Berbasis Pendidikan Karakter Siswa Kelas V Sekolah Dasar - Sumarni Bambang (Journal of Contemporary Issue in Elementary Education, 2023)
This study aims to find out whether there is an effect of the Cooperative Integrated Reading and Composition (CIRC) method on the reading comprehension ability based on character education of elementary students in discourse text material. The research subjects consisted of two schools, namely SDN 44 Kota Ternate as the experimental class and SDN 45 Kota Ternate as the control class. Research subjects were determined based on the results of the average pretest and posttest scores. The research design used in this study was a quasi-experimental research design involving experimental and control groups, with a non-equivalent control group design. Students' character education-based reading comprehension ability was measured using a multiplechoice test. Measurement results data were analyzed using the t-test with the help of the SPSS 16.0 for Windows program. The results of this study indicated that the average percentage value increased so that learning using the Cooperative Integrated Reading and Composition (CIRC) method on students' reading comprehension skills was higher 76, 33 compared to students who study with conventional learning. Research data analysis techniques were carried out by descriptive analysis and statistical analysis using a t-test with a significance of 0.050 for hypothesis testing. For this reason, based on the results of this study, it can be concluded that the application of the Cooperative Integrated Reading and Composition (CIRC) method can affect the ability to read comprehension based on character education in fifth grade elementary school students.